2022
DOI: 10.1111/cns.13824
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cognitive reserve proxies on cognitive function and frontoparietal control network in subjects with white matter hyperintensities: A cross‐sectional functional magnetic resonance imaging study

Abstract: Aims This study aimed to analyze the potential association between cognition reserve (CR) components, including education, working activity, and leisure time activity, and cognitive function in subjects with white matter hyperintensities (WMH). The study also explored the role of the frontoparietal control network (FPCN) in such association. Methods White matter hyperintensities subjects with and without cognitive impairment (CI) were evaluated with multimodal magnetic resonance imaging, neuropsychological tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…Twenty-one studies [22,23,[25][26][27][28][29][30][31][32][33][36][37]40,[42][43][44][45][46][47] recorded number of subjects that underwent education. The results discovered a significant difference between the control (n = 793) and VCI (n = 651).…”
Section: Educational Experiencementioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-one studies [22,23,[25][26][27][28][29][30][31][32][33][36][37]40,[42][43][44][45][46][47] recorded number of subjects that underwent education. The results discovered a significant difference between the control (n = 793) and VCI (n = 651).…”
Section: Educational Experiencementioning
confidence: 99%
“…Higher MMSE scores show better mental capability's score of 24 following educational correction is suggested for patients with VCI [49]. Twenty studies [22][23][24][25][26][27][28][30][31][32][33][34][35][37][38][39][40]44,46,47] collected MMSE scores. There was a statistically significant difference between the two groups.…”
Section: Mmse Scorementioning
confidence: 99%
See 1 more Smart Citation
“…Understanding how SVD and CR collectively influence the brain network is pivotal in preventing cognitive impairment. Existing studies have effectively examined the focal frontoparietal control network backbones (Chen et al, 2022; Ye et al, 2022). However, they may not comprehensively capture the collective network effect of SVD and CR.…”
Section: Introductionmentioning
confidence: 99%
“…Error bars indicate standard deviation, **p < 0.01, ***p < 0.001. CON, control group; M-UL, Fugl-Meyer Assessment Upper Limb; MIT, motor imagery training groupEmerging neuroimaging studies have identified neuroimaging biomarkers of functional recovery in stroke patients [39][40][41]. Using multimodal neuroimaging approaches, recent discoveries have revealed brain responses to interventions targeting motor function, including brain atrophy alleviation,42 selective disruption of sensorimotor circuits,43,44 different cortical recruitment patterns,9 and intrinsic brain network reorganization 33.…”
mentioning
confidence: 99%